ANALISIS KARAKTERISTIK VOLUME LALU DI JALAN TOL SEMARANG - Mauren Ninata Shiky; Ronald Jeferson Simbolan; Ismiyati Ismiyati; Epf. Eko Yulipriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Developing facilities and infrastructures on the highway in the form of planning, operational designing, and research need the value of Annual Average Daily Traffic (AADT) is a very important factor, necessary survey traffic volume for one year by a collector's gate toll, (365 days) will be a need of time and cost, so, to predict AADT is used data traffic of previous year.Secondary data obtained from the permanent counter PT. Jasamarga (Persero). Tbk Semarang AADT 2013 and 2014 at the toll gate section A (Manyaran-Jatingaleh), section B (Jatingaleh-Tembalang), and section C (Jatingaleh-Muktiharjo) Data Analysed good for obtaining characteristic and to predict value AADT with expansion factor. Based on analysis the characteristic at Semarang tollway, hourly traffic pattern increasing at busy hours and single peak hour 6% from ADT. Daily traffic pattern increasing active day around 12-16% and decreasing at weekend around 4% and the annual traffic pattern of urban variation behavior with different needs of individual route in mobility and the value of hourly expansion factor for section A 16,98-52,44,section B 15,99-76,46 and section C 16,21-69,44, daily expansion factor section A 6,63-7,95, section B 3,75-4,21 and section C 6,61-7,97 ,monthly expansion factor section A 0,83-1,081,section B 0,55-1,18 and section C 0,82-1,068 with confidence level 68,7%. applicable to next year AADT predictions.